PENYELENGGARAAN SISTEM JAMINAN SOSIAL (SJS) DI INDONESIA DALAM PERSPEKTIF INTERNASIONAL - Purwoko, Bambang (L2Dikti Wilayah III, 2017)
The implementation of social security in an international perspective has been directed at the social protection systems need to have the coordination of various things, among others: (1) the availability of employment, (2) health care facilities and (3) the role of labor market in the reemployment of employees having layoff to new employment in order to ensure the sustainability of their social security system. The purpose of this research was to compare social security in the us, Korea and China so that it can be taken as an example implementation in Indonesia. The method used is the study of librarianship with a descriptive exploratory approach. The method used is the study of library research with a descriptive exploratory approach. It can be concluded that: (1) conducting of social security in the US., South Korea and China have been well protected with the availability of work and the existence of permanent employment market presence. (2) Conducting SJSN by BPJS in Indonesia is still exclusive, has yet to reach the protection of workers as a whole, because membership of the workers against the labor force is still less than 25%, due to the stakeholders’ intervention.